1995
DOI: 10.1172/jci118244
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci for blood pressure and cardiac mass in the rat by genome scanning of recombinant inbred strains.

Abstract: In the HXB and BXH recombinant inbred strains derived from the spontaneously hypertensive rat and the normotensive Brown Norway rat, we determined the strain distribution patterns of 500 genetic markers to scan the rodent genome for quantitative trait loci regulating cardiac mass and blood pressure. The markers spanned 1,139 cM of the genome and were tested for correlations with left ventricular mass adjusted for body weight, and with systolic, diastolic, and mean arterial pressures. The marker for the dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 42 publications
7
88
1
Order By: Relevance
“…On the other hand, genetic loci for cardiac mass that are independent of the influence of blood pressure have been found on rat chromosomes 2, 20 3, 9 10, 23 12, 24,25 and 17. 26 The latter QTL was close to the Edn1 and Drd1A genes on the short arm of rat chromosome 17 (17p14), at least 40 cM away from the QTL we describe in the present study. It is important to emphasize that none of the above studies provided substantive evidence of functional differences or genetic sequence variation implicating a particular gene in the control of cardiac mass.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, genetic loci for cardiac mass that are independent of the influence of blood pressure have been found on rat chromosomes 2, 20 3, 9 10, 23 12, 24,25 and 17. 26 The latter QTL was close to the Edn1 and Drd1A genes on the short arm of rat chromosome 17 (17p14), at least 40 cM away from the QTL we describe in the present study. It is important to emphasize that none of the above studies provided substantive evidence of functional differences or genetic sequence variation implicating a particular gene in the control of cardiac mass.…”
Section: Discussionsupporting
confidence: 63%
“…A genome-wide QTL analysis undertaken in another laboratory, using 500 genetic markers to genotype recombinant inbred strains of rats (HBX and BXH) derived from a spontaneously hypertensive strain and a normotensive strain, 11 indicated the presence of blood-pressure regulatory loci on rat chromosomes 2, 4, and 19. The IL-6 marker on chromosome 4 showed the strongest correlation with mean arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported BP QTLs in the same region in 3 different F 2 intercrosses (Table 2). [22][23][24][25][26][27][28][29][30][31][32][33] We found that the angiotensin receptor 1a gene (Atr1a) is in this putative QTL region. All published heart weight/hypertrophy QTLs on chromosome 17 harbor a common interesting candidate gene, Drd1a (dopamine receptor 1a).…”
Section: Bilusic Et Al Genetic Analysis In the Lyon Hypertensive Ratmentioning
confidence: 99%